Vilnius - žydų bundo centras XIX amžiaus pabaigoje - Vyšniauskas, Arūnas (Lietuvos istorijos studijos, 1996)
The article deals with the role of the Jewish Social Democrats of Vilnius in the process of the consolidation of the Russian Social Democratic movement. In the autumn of 1897, the General Jewish Workers' Union in Russia and Poland was established in Vilnius. Earlier, in the summer of that year, an important agreement was concluded in Switzerland between A. Kremer, the leader of the Jewish Social Democrats of Vilnius, and G. Plekhanov's Group. A. Kremer received written authorizations to convene a constituent congress of the Russian Social Democrats. It was decided at the 1st Congress of the Russian Social Democratic Workers' Party, which took place in Minsk (about 200 km away from Vilnius) in the spring of 1898, that the Jewish Bund was an incorporated part of the RSDWP. Five of the 9 participants in the 1st Congress of the RSDWP were Jews, with 3 representatives among them of the Bund from Vilnius.The Jewish Social Democrats of Vilnius still did not raise the idea of the Jewish national revival in 1898, nor did they recognize the importance of the national idea in general. The Bundists spoke out, inter alia, against Lithuania as an independent state, separated from Russia. In 1899-1900, a political break took place among the Bundists. The essence of this break was expressed perhaps most explicitly by M. Goldman (Liber). He urged his associates to give up cosmopolitanism and to focus on their Jewish identity on the basis of the Yiddish language. While coming out for cultural and national autonomy of the Jews, however, Jewish Social Democrats of Vilnius remained supporters of the state integrity of the Russian Empire.